Dysbiosis of Gut Microbiota and Short-Chain Fatty Acids in Encephalitis: A Chinese Pilot Study - Xu, Ruoting; Tan, Chuhong; He, Yan; Wu, Qiheng; Wang, Huidi; Yin, Jia (Frontiers in Immunology, 2020)
Background: Encephalitis, the inflammation of the brain, may be caused by an infection or an autoimmune reaction. However, few researches were focused on the gut microbiome characteristics in encephalitis patients. Methods: A prospective observational study was conducted in an academic hospital in Guangzhou from February 2017 to February 2018. Patients with encephalitis were recruited. Fecal and serum samples were collected at admission. Healthy volunteers were enrolled from a community. Disease severity scores were recorded by specialized physicians, including Glasgow Coma Scale (GCS), Sequential Organ Failure Assessment (SOFA) and Acute Physiology and Chronic Health Evaluation-II (APACHE-II). 16S rRNA sequence was performed to analyze the gut microbiome, then the α-diversities and β-diversities were estimated. Short-chain fatty acids (SCFAs) were extracted from fecal samples and determined by gas chromatography-mass spectrometry. Serum D-lactate (D-LA), intestinal fatty acid-binding protein (iFABP), lipopolysaccharide (LPS), and lipopolysaccharide-binding protein (LBP) were measured by enzyme-linked immunosorbent assay (ELISA). The associations among microbial indexes and clinical parameters were evaluated by Spearman correlation analysis. Results: In total, twenty-eight patients were recruited for analysis (median age 46 years; 82.1% male; median GCS 6.5; median SOFA 6.5; median APACHE-II 14.5). Twenty-eight age- and sex-matched healthy subjects were selected as controls. The β-diversities between patients and healthy subjects were significantly different. The α-diversities did not show significant differences between these two groups. In the patient group, the abundances of Bacteroidetes, Proteobacteria, and Bacilli were significantly enriched. Accordingly, fecal SCFA levels were decreased in the patient group, whereas serum D-LA, iFABP, LPS, and LBP levels were increased compared with those in healthy subjects. Correlation analyses showed that disease severity had positive correlations with Proteobacteria and Akkermansia but negative correlations with Firmicutes, Clostridia and Ruminococcaceae abundances. The cerebrospinal fluid albumin-to-serum albumin ratio (CSAR) was positively related to the α-diversity but negatively correlated with the fecal butyrate concentration. Conclusion: Gut microbiota disruption was observed in encephalitis patients, which manifested as pathogen dominance and health-promoting commensal depletion. Disease severity and brain damage may have associations with the gut microbiota or its metabolites. The causal relationship should be further explored in future studies.